CLASSIFICATION OF SOILS FROM RIVER ISLAND MICRODEPRESSIONS (GREAT WAR ISLAND, SERBIA): SOIL CLASSIFICATION OF ISLAND MICRODEPRESSIONS - Radmanović, Svjetlana B.; Bogosavljević, Jelena; Dugonjić, Mladen; Đorđević, Aleksandar (Journal of Agricultural Sciences (Belgrade), 2025)
Great War Island is a river island formed at the confluence of the Sava and Danube rivers, heavily exposed to groundwater and flooding and is therefore suitable as a case study for the investigation of soil hydromorphism. The aim of this study was to comprehensively classify the soils in two somewhat different microdepression on Great War Island according to the local and international WRB 2022 and USDA Soil Taxonomy systems, with particular attention to the soil-forming factors and properties that influenced soils classification. The soil of the closed microdepression is Eugley, Hipogley, Mineral, Calcareous or Calcaric Oxygleyic Gleysol (Loamic, Humic). The soil of the microdepression open to the Danube is Humogley, Calcareous, Weakly alkalized, Loamy or Calcaric Oxygleyic Mollic Tidalic Gleysol (Loamic, Fluvi-Loaminovic). The high level and amplitude of the groundwater and the longer duration of the flood caused by the topography, as well as the characteristics of the alluvial sediments, are the main soil-forming factors that have influenced the classification of the soils. The local soil classification reflects most of the soil-forming factors/characteristics as the two international soil classifications. To avoid possible misunderstandings and increase accuracy, quantitative thresholds for soil type and lower levels are required.